A Call for a Better Understanding of Aquatic Chytrid Biology - Laundon, Davis; Cunliffe, Michael (Frontiers in Fungal Biology, 2021)
The phylum Chytridiomycota (the ‘chytrids’) are an early-diverging, mostly unicellular, lineage of fungi that are significant aquatic saprotrophs, parasites, and pathogens, and of evolutionary interest because they retain biological traits considered ancestral in the fungal kingdom. While the existence of aquatic chytrids has long been known, their fundamental biology has received relatively little attention. We are beginning to establish a detailed understanding of aquatic chytrid diversity and insights into their ecological functions and prominence. However, the underpinning biology governing their aquatic ecological activities and associated core processes remain largely understudied and therefore unresolved. Many biological questions are outstanding for aquatic chytrids. What are the mechanisms that control their development and life cycle? Which core processes underpin their aquatic influence? What can their biology tell us about the evolution of fungi and the wider eukaryotic tree of life? We propose that the field of aquatic chytrid ecology could be further advanced through the improved understanding of chytrid biology, including the development of model aquatic chytrids.